Dengue Fever and Graves’ Disease Complicated with Guillain-Barré Syndrome: A Case Report - Fatimah Eliana Taufik; Juhan Khalila (PP PERKENI, 2024)
GBS is a rare neurological autoimmune disorder in which a person’s immune system mistakenly attacks part of peripheral nervous system and the network of nerves that carries signals from the brain and spinal cord to the rest of the body. GBS is not commonly found alongside Graves’ disease or dengue fever. 35-year-old woman who have been previously diagnosed with Graves’ disease with dengue fever and GBS. On the fifth day of treatment, she showed signs of poor respiratory function, weak neck muscle power, paralyzed and was indicated for intubation. The cerebrospinal fluid analysis showed a consistent finding of GBS of albumin cytological dissociation with an increased level of protein of 80 mg/dL, glucose 50 mg/dL, and a normal lymphocytes cell count of 4/cmm without polymorphs. She was ventilated for three days and began to receive the treatment of intravenous immunoglobulins (IVIG) of 0.4 g/kg/day for a total of five days and remarkable recovery and was extubated on day 3 of IVIG. The case study theorises those endogenous factors, such as gangliocytes and ICAM-1, as well as exogenous factors such as bacterial and viral infection, may play a part in the simultaneous presentation of GBS and Graves’ disease. Antibodies that formed from these factors have an affinity to GM1 and GT1A gangliosides which are typically exposed on the plasma membrane and can cause molecular mimicry as well as cytokine stimulation which is the main feature of GBS. Furthermore, it is thought that preceding infection of dengue virus may also lead to the development of GBS. Intravenous immunoglobulin therapy shows a promising result on treating a simultaneous case of GBS presenting in patient with Graves’ disease and dengue fever.